Prospect of indigenous plant species for revegetation in the tailings area of ex community gold mine - WIWIK EKYASTUTI; DWI ASTIANI; EMI ROSLINDA (Biodiversitas Journal of Biological Diversity, 2016)
Ekyastuti W, Astiani D, Roslinda E. 2016. Prospect of indigenous plant species for revegetation in the tailings area of ex community gold mining. Biodiversitas 17: 764-768. One of the reclamation activities in the tailings area of ex community gold mine is revegetation. The success of revegetation is strongly influenced by the selection of suitable plant species. The purpose of this research was to determine the prospects of indigenous plant species for revegetation in the tailings area of ex community gold mine. Research has been conducted at the tailings area of ex community gold mining in Menjalin subdistricts Landak District West Kalimantan, using an experiment method with randomized complete block design (RCBD). Used ss basic for blocking is the difference of tailings area age: 2 years old and 10 years old after mining activities. In both locations, seven indigenous plant species were planted, i.e: Dillenia suffruticosa, Vitex pinnata, Archidendron pauciflorum, Anacardium occidentale, Shorea leprosula, Alstonia scholaris and Hevea brasiliensis. The results showed that the seven indigenous plant species are tolerant to mercury and can grow well in the tailing areas of ex community gold mine of both 2-years and 10-years after mining. Five indigenous plant species use phytostabilization to remediate mercury in the plant tissue, while two others species use phytoextraction. Therefore, the prospect of using indigenous plant species for revegetation in tailings area of ex community gold mine is very well. Keywords: Ex community gold mining, indigenous plant species, tailing